(untitled) (Международный научный журнал «Инженер», 2025)
In this article shows the adverse health effects of industrial vibration on workers exposed to hand-transmitted vibration and whole-body vibration. Long-term exposure impairs the nervous, circulatory, musculoskeletal, and skeletal systems. Hand-transmitted vibration can cause Hand–Arm Vibration Syndrome, characterized by numbness, tingling, white‑finger episodes, reduced grip strength, and musculoskeletal issues a progression confirmed. Whole-body vibration exposure, commonly experienced by heavy machinery operators, link to back and spinal disorders, fatigue, gastrointestinal issues, and potential cardiovascular complications. Also, the article gives protection measures based on occupational health regulations, including ERGONOMIC ENGINEERING CONTROLS, administrative practices like work-rest rotations and health monitoring, and use of anti-vibration equipment . These interventions align with European Directive 2002/44/EC, which mandates risk assessments and exposure monitoring. The study concludes that an integrated approach combining technical controls, organizational strategies, and personal protection is essential to mitigate vibration hazards and safeguard workers’ health in industrial settings.